If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 3x + 2 = 5x + 6 Reorder the terms: 2 + X + 3x = 5x + 6 Reorder the terms: 2 + X + 3x = 6 + 5x Solving 2 + X + 3x = 6 + 5x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + X + -2 + 3x = 6 + -2 + 5x Reorder the terms: 2 + -2 + X + 3x = 6 + -2 + 5x Combine like terms: 2 + -2 = 0 0 + X + 3x = 6 + -2 + 5x X + 3x = 6 + -2 + 5x Combine like terms: 6 + -2 = 4 X + 3x = 4 + 5x Add '-3x' to each side of the equation. X + 3x + -3x = 4 + 5x + -3x Combine like terms: 3x + -3x = 0 X + 0 = 4 + 5x + -3x X = 4 + 5x + -3x Combine like terms: 5x + -3x = 2x X = 4 + 2x Simplifying X = 4 + 2x
| -2x^2+20x-36=0 | | -2x^2+20x-39=0 | | 2(x+5)-x=x+10 | | 4x-3=2x-1/3 | | 45=9x+9 | | (Y)+y=2 | | -10x-17=167 | | 3*x+20=5*x-4 | | 4a^5-500a^2=0 | | 68hm=km | | r^2+12r-189=0 | | 9w+1+3(w+2)= | | 8x-14=x^2+x-2 | | 3-(4x-3)=1 | | -45+m=24 | | 6n-24=9-3n-3 | | K^2+8=56 | | p(2+5p)= | | 3/2=x/11 | | 2x-35(4+5)=40 | | 2lnx-1= | | (4x-52)+(x+32)+(.5x+46)= | | x-5=5+x | | 2z+12=3-z | | 3x+5+2x-1=3x+17 | | 6a-8=3a+7 | | 7x-2x+7=2x+32 | | 8+2(8x-6)=2(4+7) | | (10x-20)+(x+52)+(.125x+59)= | | -7x-22=-141 | | 9p-3=21+p | | (3x-66)+(x+18)+(.17x+53)= |